Project Activity Management by Revenue Planner and Quality Dashboard Tools - Jain, Neha (My University, 2018)
Every corporation or institution needs an efficient tool for data organization and data maintenance. Doing it manually is very difficult as well as complex. Project passes through development, testing, maintaining phases and it is the complex, critical and long term process. Therefore, it is not feasible to maintain all these activities manually. Managerial tasks like planning project, assigning task to different teams, tracking status of projects and checking resource availability, all are performed manually which is not feasible at big level organization. At some interval manager needs performance and analysis reports to check the progress of project. Effective management and technical support are required to accomplish the required goal. Thus, we need efficient tools for the same. Budget Editor tool is used for the same reasons. It is an automated efficient data governance tool, basically used for Business Administration Platform Management. It provides user interface which is made in Microsoft Excel from where user can extract and analyze data in tabular format as well as regular format. Various type of reports can be generated using this tool which contains required data with default conditions and calculations.
Keywords: Visual Basic Application; Macros; XML; Parsing